Massive renal size is not a contraindication to a laparoscopic approach for bilateral native nephrectomies in autosomal dominant polycystic kidney disease (ADPKD). (16th August 2014) - Wisenbaugh, Eric S.; Tyson, Mark D.; Castle, Erik P.; Humphreys, Mitchell R.; Andrews, Paul E.
<x xml:space="preserve">Abstract</x> Objective To determine if massive renal size should be a contraindication for attempting a laparoscopic approach to bilateral native nephrectomies in patients with autosomal dominant polycystic kidney disease (ADPKD). Patients and Methods We retrospectively reviewed all laparoscopic bilateral nephrectomies performed for ADPKD at our institution from 1 January 2000 to 31 December 2012. We stratified patients by kidney weight (with or without at least one kidney weighing >2500 g) and compared perioperative data, complications, and status of kidney allografts. Additionally, the subset of patients with at least one kidney weighing >3500 g was compared with the rest of the cohort. Results We identified 68 patients; mean (range) individual kidney weight was 1984 (197–5042) g. In all, 24 patients had at least one kidney weighing >2500 g, yet patients in this group were not significantly different from the rest of the cohort for complications, estimated blood loss, transfusion rate, or duration of hospitalisation. For those who underwent simultaneous renal allotransplantation, native kidney size was not associated with graft outcomes. Additionally, of the six patients with at least one kidney weighing >3500 g, only one required a blood transfusion, and the group had no intraoperative or postoperative Clavien grade ≥3 complications. None of the cohort required conversion to open surgery. Conclusion Massive size of polycystic kidneys is not a contraindication to attempting a laparoscopic approach to bilateral nephrectomies in an experienced, high‐volume centre.